CONTRADICTIONS IN FORMATION OF AN INNOVATIVE MODEL OF ECONOMIC DEVELOPMENT OF UKRAINE - V. Zianko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article has been investigated the basic economic contradictions inherent to the current stage of formation in Ukraine model of innovative development, their causes and consequences for the national economy were analyzed; reasonable ways of enhancing the development of innovative business solutions as a basic condition of existing economic contradictions were corroborated.